Ω-3 Fatty acids for major depressive disorder in adults: an abridged Cochrane review. Issue 3 (2nd March 2016) - Appleton, Katherine M; Sallis, Hannah M; Perry, Rachel; Ness, Andrew R; Churchill, Rachel
Abstract : Objective: To assess the effects of n-3 polyunsaturated fatty acids (n-3PUFAs; also known as ω-3 fatty acids) compared with comparator for major depressive disorder (MDD) in adults. Design: Systematic review and meta-analyses. Data sources: The Cochrane Depression, Anxiety and Neurosis Review Group's Specialised Registers (CCDANCTR) and International Trial Registries searched to May 2015. CINAHL searched to September 2013. Trial selection: Inclusion criteria: a randomised controlled trial (RCT); that provided n-3PUFAs as an intervention; used a comparator; measured depressive symptomology as an outcome; and was conducted in adults with MDD. Outcomes: Primary outcomes were depressive symptomology and adverse events. Results: 20 trials encompassing 26 relevant studies were found. For n-3PUFAs versus placebo, n-3PUFA supplementation resulted in a small-to-modest benefit for depressive symptomology: SMD=−0.32 (95% CI −0.52 to −0.12; 25 studies, 1373 participants, very low-quality evidence), but this effect is unlikely to be clinically meaningful, is very imprecise and, based on funnel plot inspection, sensitivity analyses and comparison with large well-conducted trials, is likely to be biased. Considerable evidence of heterogeneity between studies was also found, and was not explained by subgroup or sensitivity analyses. Numbers of individuals experiencing adverse events were similar in intervention and placebo groups (OR=1.24, 95% CI 0.95 to 1.62; 19 studies, 1207 participants; very low-quality evidence). For n-3PUFAs versus antidepressants, no differences were found between treatments in depressive symptomology (MD=−0.70 (95% CI −5.88 to 4.48); 1 study, 40 participants, very low-quality evidence). Conclusions: At present, we do not have sufficient evidence to determine the effects of n-3PUFAs as a treatment for MDD. Further research in the form of adequately powered RCTs is needed.